Preparation and characterization of glass ceramics synthesized from lead slag and lead-zinc tailings. Issue 10 (15th May 2023) - Zhang, Xiaoguang; Li, Lili; Hassan, Qadeer Ul; Pan, Dean; Zhu, Gangqiang
Abstract: Using lead slag and lead-zinc tailings to prepare high-value glass-ceramic can realize the comprehensive utilization of solid waste and reduce the environmental pollution caused by lead slag landfill. Firstly, lead-zinc tailings and borax are used to melt and temper lead slag to improve its sintering performance. At 1450 °C, the lead slag melted and tempered by adding 40% lead-zinc tailings and 4% borax has good fluidity in the molten state. In water quenching, crystallization is not easy, and the water quenching slag has good sintering performance. Then, the water-quenched slag obtained by melting and tempering lead slag with lead-zinc tailings and borax was ball-milled and mixed with 10% albite feldspar and sintered at 1050 °C for 90 min to prepare glass ceramics. The prepared glass-ceramics have excellent performance parameters such as bulk density of 2.79 g/cm 3, water absorption of 0.05%, the flexural strength of 102.18 MPa, acid resistance of 0.15%, and alkali resistance of 0.032%. Simultaneously, the glass ceramics exhibited excellent resistance to the leaching of heavy metals where the leaching concentrations of Pb, Zn, As, and Cd were 0.125, 1.268, 0.324, and 0.029 mg/L, respectively. This research can provide a new idea for comprehensively utilizing solid waste.